Utilization of SPSS Application as A Data Analysis Tool For Various Research Needs - Azkyatul Mardiyah; De Ajeng Vien Saputri; Novaneza Rasendriya; Syahdan Jamjami; Purwadi Purwadi (INDO PUBLISHING, 2026)
The development of information technology has significantly changed the way research data is processed and analyzed. One of the software that is often used is IBM SPSS, which functions to perform statistical analysis quickly and organized. This study aims to study the use of SPSS applications as a tool to analyze data for various research needs and evaluate the extent to which the application is effective in assisting the data processing process. The method used is a literature study that involves collecting and analyzing various journals, scientific articles, as well as previous research that discusses the use of SPSS in various academic and research activities. The research stages include determining the problem, reading existing material, collecting information, analyzing data using SPSS, evaluating the results, and concluding the research.